Selaginella daozhenensis (Selaginellaceae), a new lycophyte from a limestone cave in northern Guizhou, China - Sun, Qing-Wen; Zhao, Jun-Hua; Zhang, Libing (Phytotaxa, 2015)
Selaginella daozhenensis, a new species of the lycophyte genus Selaginella (Selaginellaceae) from a limestone cave in northern Guizhou, China is described and illustrated. The new species is morphologically most similar to S. labordei and S. sichuanica but is distinct by its leaves being bluish green when fresh, its median leaves having aristae as long as leaf lamina, and its lateral leaves being larger (3.5–5.0 × 1.7–2.5 mm). Selaginella daozhenensis is currently known only from a single limestone cave and is considered to be Critically Endangered (CR), based on IUCN Red List criteria. It is also argued that S. sichuanica, earlier wrongly synonymized with S. labordei in treatments of the genus, should be recognized.